Penerapan Konseling Adiksi Narkoba di Balai Rehabilitasi Badan Narkotika Nasional (BNN) Tanah Merah Samarinda - Rudy Hadi Kusuma (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
In East Kalimantan, many people use Substance Use Disorders (GPZ) due to drug use that require counseling services in rehabilitation. Related research to study the qualifications and competencies of counselors involving drug counseling, techniques used, evaluation, coordination and solutions in the application of drug counseling at the National Narcotics Rehabilitation Agency (BNN) Tanah Merah-Samarinda. This research uses descriptive qualitative method. Data sources consist of primary and secondary data sources. Collection techniques used are interviews, observation, and study documentation. Data analysis techniques consist of data reduction, data display, conclusion drawing. The technique of checking validity data uses credibility, transferability, dependability, and confirmability. The results showed that this study involved 13 people, 11 people from health education and 1 psychologist. Counseling techniques used consist of individual counseling, group counseling and family counseling as well as cognitive and behavioral therapy (CBT). Clients receive experience and knowledge to support healthy and proven life. The hard character of the client and the negative family stigma often become difficult in providing services. However, through the approval of individual humanists, patience and high service commitment can work well.